Numerical investigation on effect of particle aspect ratio on the dynamical behaviour of ellipsoidal particle flow. (30th August 2021) - Hossain, M; Zhu, H P; Yu, A B
Abstract: Flow of ellipsoidal particles in a modal shear cell was investigated at the microdynamic level based on discrete element method simulations. In a stress-controlled double-shear condition, the flow was studied by varying the aspect ratio of ellipsoidal particles and comparing with the flow of spherical particle assembly in terms of some key properties, including particle alignment, linear velocity, angular velocity, porosity, contact force and contact energy. It was found that particle elongation impacts the rotational displacement around the axis perpendicular to the shear direction, which causes that the ellipsoidal particles with higher elongation are more aligned with the direction of the shear velocity, with more uniform force network. This then affects other particle properties. The fluctuation of linear velocity and the angular velocity decreases with an increase in particle aspect ratio, although the particle elongation does not significantly affect the flow velocity gradient. There is a reduction in both normal and tangential forces per contact with an increase of particle elongation. Due to the variation of the particle alignment with elongation, the standard deviation of the contact energies increases and then reduces when an increase in particle aspect ratio occurs, and on contrary, the porosity has an opposite variation trend.